Hair: more than just an appendage - Reddy, Harshitha; Shanmugam, Srikanth; Karunanandhan, Manobalan (International Journal of Research in Dermatology, 2021)
Hypotrichosis is a relatively common feature of a number of complex hereditary syndromes. However, the isolated variant, called hereditary hypotrichosis simplex (HHS), is uncommon. We present a 4 years old child and his father who presented to us with features suggestive of HHS. No other associated ectodermal and systemic abnormalities were noted.